2020
DOI: 10.2196/19684
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use, eHealth Literacy, Disease Knowledge, and Preventive Behaviors in the COVID-19 Pandemic: Cross-Sectional Study on Chinese Netizens

Abstract: Background Since its outbreak in January 2020, COVID-19 has quickly spread worldwide and has become a global pandemic. Social media platforms have been recognized as important tools for health-promoting practices in public health, and the use of social media is widespread among the public. However, little is known about the effects of social media use on health promotion during a pandemic such as COVID-19. Objective In this study, we aimed to explore th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
235
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(261 citation statements)
references
References 67 publications
17
235
2
7
Order By: Relevance
“…In agreement with the findings described in our paper, Kubb & Foran did not observe a meaningful contribution of eHL to a parent's change of stress level when searching the web for current somatic health issues related to their own or their children's symptoms [97]. However, there is one study reporting that eHL positively moderates the relationship between the frequency of using social media and preventive behaviours [98].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the findings described in our paper, Kubb & Foran did not observe a meaningful contribution of eHL to a parent's change of stress level when searching the web for current somatic health issues related to their own or their children's symptoms [97]. However, there is one study reporting that eHL positively moderates the relationship between the frequency of using social media and preventive behaviours [98].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found that the mean time spent on reading COVID-19 news was 1.8 hours per day for the pregnant women, which was slightly shorter than the general population (2.4 hours) reported in other studies [ 21 ]. The worry of radiation from phones or computers among pregnant women might be related to their relatively shorter time spent on social media.…”
Section: Discussioncontrasting
confidence: 56%
“…The Impact of Event Scale-Revised (IES-R) has 22 items that measure psychological distress after exposure to a crisis. The total IES-R score was categorized as normal (0-23), mild (24)(25)(26)(27)(28)(29)(30)(31)(32), moderate (33)(34)(35)(36), and severe (≥37) [14]. The IES-R questionnaire has been used in the Vietnamese population in previous studies [14][15][16].…”
Section: Impact Of Event Scale-revisedmentioning
confidence: 99%
“…The total score range for each domain was 0 to 42. The level of each domain was interpreted as normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) for the depression subscale; normal (0-6), mild (7-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe for the anxiety subscale; and normal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18), moderate…”
Section: Impact Of Event Scale-revisedmentioning
confidence: 99%